PROTOTYPE GROUNDING DETECTOR PADA GROUND CLUSTER DENGAN SISTEM INTERLOCKPADALBS (LOAD BREAK SWITCH) BERBASIS ARDUINO MEGA 2560 DENGAN TAMPILAN HMI (HUMAN MACHINE INTERFACE) - Pasaribu, Bambang Handoko; Setiono, Iman (Gema Teknologi, 2018)
Electricity has become a daily necessity in the community both social, economic and business. Therefore electricity is needed every day and it is the reliability of PLN. To fulfill such reliability While the reliability of electrical energy should be followed by inspection on the equipment used. PLN field employees themselves who every day always do inspection on the network of all the repeaters, so that field officers always know the state of the network in the field. If the network looks bad or requires maintenance it will be scheduled to do the job. Before the holding of the work it will be done in the first outage area is to operate the switching tool didaerah area. The switching tools are ABSW and LBS. After all the swithing tools are operated the workers always do the grounding first on the three phases by using ground clusters at the starting point to the end of the work where if transmitted so called PMS ground. This is done as a safety because the LBS switching tool is closed so that workers are not sure if the network has been extinguished and as a safety if LBS failed to work or failure. But here the worker himself sometimes still not sure whether the ground cluster is already installed properly or not. And as a safeguard against the occurrence of any maneuvering done by employees from the office Rayon. Therefore the author wants to make a prototype to detect whether grounding is installed properly or not in every phase. The prototype uses Arduino mega as its micron and uses a voltage sensor to find out the value of the voltage. If the ground claster is installed and work fails on LBS then the OCR relay will work and PMT will trip. With the prototype is expected to improve security in the work and minimize the occurrence of work accidents. This prototype has a 0% chance of a crash if the ground cluster is properly installed.Â